Giant axillary tumor resection using ultrasound-guided interscalene brachial plexus block and serratus anterior plane block. Issue 9 (September 2020) - Luo, Ruimin; Gu, Yu; Deng, Xu; Wu, Wenfeng; Yao, Yonghua
Herein, we report the combined use of interscalene brachial plexus block and serratus anterior plane block for surgical removal of a large neoplasm that was embedded deep in the axilla and chest wall of a patient with high-risk hypertension. With the combined use of conventional and novel nerve blocks, the large neoplasm was successfully resected without obvious complications.